Digital Transformation In Vocational Education: Theoretical Basis For Increasing The Efficiency Of Management Decision-Making - Boboev Farrukh Akhmedjonovich (Genius Journals, 2025)
This article theoretically analyzed the impact of digital transformation processes on the management system of vocational education and training (VET) institutions. The limitations and inefficiency of traditional management paradigms in the context of the digital economy were studied. Classical theories of educational management and decision-making (formal, rational, collegial, political, etc.) were critically analyzed, and their inability to meet modern challenges was substantiated. Based on this analysis, new theoretical approaches were proposed, which integrate the principles of data-driven decision-making and agility. Key principles such as contextual agility, data-informed iteration, stakeholder integration, and strategic foresight were identified, and their theoretical essence was revealed.
Keywords: Digital transformation; vocational education; effectiveness; education management